Academic Librarians’ Educational Factors and Perceptions of Teaching Transformation: An Exploratory Examination - Nichols Hess, Amanda (Evidence Based Library and Information Practice, 2019)
Objective – As information literacy instruction is an increasingly important function of academic librarianship, it is relevant to consider librarians’ attitudes about their teaching. More specifically, it can be instructive to consider how academic librarians with different educational backgrounds have developed their thinking about themselves as educators. Understanding the influences in how these shifts have happened can help librarians to explore the different supports and structures that enable them to experience such perspective transformation.Methods – The author electronically distributed a modified version of King’s (2009) Learning Activities Survey to academic librarians on three instruction-focused electronic mail lists. This instrument collected information on participants’ demographics, occurrence of perspective transformation around teaching, and perception of the factors that influenced said perspective transformation (if applicable). The author analyzed the data for those academic librarians who had experienced perspective transformation around their teaching identities to determine if statistically significant relationships existed between their education and the factors they reported as influencing this transformation.Results – Results demonstrated several statistically significant relationships and differences in the factors that academic librarians with different educational backgrounds cited as influential in their teaching-focused perspective transformation.Conclusion – This research offers a starting point for considering how to support different groups of librarians as they engage in information literacy instruction. The findings suggest that addressing academic librarians’ needs based on their educational levels (e.g., additional Master’s degrees, PhDs, or professional degrees) may help develop productive professional learning around instruction.